Next-generation antibody-based therapies in neurology - Ruck, Tobias; Nimmerjahn, Falk; Wiendl, Heinz; Luenemann, Jan D. (Brain, 2021)
Ruck et al. describe recent developments in next-generation antibody-based therapies for brain diseases, including progress in Fc engineering, and efforts to improve the bioavailability of antibody-based platforms in CNS parenchyma. They highlight the potential benefits as well as limitations of such therapies in neurology.
CRIS-Team WoS Importer:2022-04-29